Deficiency of G9a Inhibits Cell Proliferation and Activates Autophagy via Transcriptionally Regulating c-Myc Expression in Glioblastoma - Ke, Xiao Xue; Zhang, Rui; Zhong, Xi; Zhang, Lei; Cui, Hongjuan (Frontiers in Cell and Developmental Biology, 2020)
Glioblastoma is an aggressive and difficult to treat cancer. Recent data have emerged implicating that histone modifications level may play a crucial role in glioma genesis. The histone lysine methylthransferase G9a is mainly responsible for the mono- and di-methylation of histone H3 lysine 9 (H3K9), whose overexpression is associated with a more aggressive phenotype in cancer. However, the detailed correlations between G9a and glioblastoma genesis remains to be further elucidated. Here, we show that G9a is essential for glioblastoma carcinogenesis and reveal a probable mechanism of it in cell proliferation control. We found that G9a was highly expressed in glioblastoma cells, and knockdown or inhibition of G9a significantly repressed cell proliferation and tumorigenesis abilities both in vitro and in vivo. Besides, knockdown or inhibition of G9a led to a cell-cycle arrest in G2 phase, as well as decreased the expression of CDK1, CDK2, CyclinA2, and CyclinB1, while induced the activation of autophagy. Further investigation showed that G9a deficiency induced cell proliferation suppression and activation of autophagy were rescued by overexpression the full-length c-Myc. ChIP assay showed that G9a was enriched on the -2267 -1949 region of c-Myc promoter in LN-229 cells, and the -1949 -1630 region of c-Myc promoter in U-87 MG cells. Dual-luciferase reporter assay showed that c-Myc promoter activity was significantly reduced after knockdown or inhibition of G9a. Our study define that G9a control glioblastoma cell proliferation by transcriptionally modulate oncogene c-Myc, and provide insight into capabilities of G9a working as potential therapeutic target in glioblastoma.